Word Ladder Game in Teaching Reading English to Young Learners - Khairatun Nisa; Rahmah Fithriani (Scope : Journal of English Language Teaching, 2023)
This research focuses on finding out the effect of implementing the Snakes and Ladders Game in teaching reading. This research was conducted by applying experimental quantitative research. The aim of this research is to determine whether or not there is an influence of the Snakes and Ladders Game on the learning achievement of grade 5 students. The author took 15 students as an experimental group using the Snakes and Ladders game and 15 students as a control group using conventional methods. The population of this study was 30 students consisting of class 5. The author took two classes as a random sample to see the influence of the Snakes and Ladders game in teaching reading. Data was taken by giving a reading test into two tests: pre-test and pro-test for the experimental and control groups. The average pre-test score for the experimental group was 60.2 and post-test 85, the average pre-test score for the control group was 55.7 and the post-test 73. Therefore this shows that the average score for the pre-test the experimental group was 60.2 and the post-test was 85. the experimental group was higher than the control group. The results of t count > t table with a significance level of p=0.05 (8.5 > 2.048). the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It is recommended that English subject teachers apply the Snakes and Ladders Game as an alternative teaching medium to help and enrich students' Reading Comprehension.